Design and Implementation of Solar Tracking - Sawant, AS; Tambavekar, PM; Kokate, PD; Vichare, SS; Satheesh, J (International Journal of Computer Sciences and Engineering, 2025)
Energy crisis is the most important issue in today’s world. Conventional energy resources are not only limited but also cause environmental pollution. Renewable energy resources are getting priorities in the whole world to lessen the dependency on conventional resources. Solar energy is rapidly gaining the focus as an important means of expanding renewable energy uses. Solar cells those convert sun’s energy into electrical energy are costly and inefficient. Different mechanisms are applied to increase the efficiency of the solar cell to reduce the cost. Solar tracking system is the most appropriate technology to enhance the efficiency of the solar cells by tracking the sun. A microcontroller based design methodology of an automatic solar tracker is presented in this paper. Light dependent resistors are used as the sensors of the solar tracker. A small prototype of solar tracking system is also constructed to implement the design methodology presented here.